Long-term Safety and Tolerability of Repeated Treatments With OnabotulinumtoxinA in Children With Neurogenic Detrusor Overactivity. Issue 4 (19th April 2023) - Franco, Israel; Hoebeke, Piet B.; Dobremez, Eric; Titanji, Wilson; Geib, Till; Jenkins, Brenda; Yushmanova, Irina; Austin, Paul F.
Abstract : Purpose: OnabotulinumtoxinA is an approved treatment for neurogenic detrusor overactivity in adults inadequately managed with anticholinergics, and more recently was approved in children on the basis of a phase 3, 48-week, single-treatment study (NCT01852045). Given the paucity of long-term pediatric data, we report on the continued safety in these patients after repeated onabotulinumtoxinA treatment. Materials and Methods: This was a multicenter, double-blind, repeat-treatment extension study (NCT01852058) in patients who entered from the preceding single-treatment study. Data were integrated across both studies. All patients (5-17 years) used clean intermittent catheterization and could receive dose escalations based on response to preceding treatment (50 U, 100 U, or 200 U onabotulinumtoxinA [not to exceed 6 U/kg]). Results: Overall, 95, 90, 55, and 11 patients received 1, 2, 3, and 4 treatments with onabotulinumtoxinA, respectively, and median (quartiles) duration of follow-up was 82 (65, 94) weeks. The safety profile was similar across doses and after repeat treatments. The most common treatment-emergent adverse event during cycles 1, 2, and 3 was urinary tract infection (31%, 34%, 22%). Three serious treatment-emergent adverse events related to study treatment (3/95; 3.2%) were reported during the study, which were all cases of urinary tract infection. Annualized urinary tract infection rates post-treatment were similar to pre-screening rates. There were no cases of autonomic dysreflexia, neutralizing antibodies, and treatment-emergent adverse events related to distant spread of toxin. Conclusions: OnabotulinumtoxinA continued to be well tolerated after repeated treatments in pediatric neurogenic detrusor overactivity patients with similar safety profiles across dose groups. Treatment-emergent adverse events were primarily urological with no new safety concerns.